RETRACTED : The Effect of Career Development, Employee Engagement, Interpersonal Communication and Work Involvement on the Performance of PT. Indo Dharma Transport - Chellsa Afridhamita; Kumba Digdowiseiso (Syntax Corporation Indonesia, 2024)
The purpose of this study is to determine the effects of Career Development, Employee Engagement, Interpersonal Communication and Job Involvement for the Employee performance of PT. Indo Dharma Transport . The results of this study indicate that there is a positive and significant influence Career Development, Employee Engagement, Interpersonal Communication and Job Involvement on Employee Performance PT. Indo Dharma Transport . Regression equation Y = 0.234 (X1) + 0.305 (X2) + 0.181 (X3) + 0.221 (X4) an be predicted about the ups and downs or the size of employee performance or the increase of employee performance at PT. Indo Dharma Transport. This is because the condition of the required needs of employees, so that PT. Indo Dharma Transport should pay attention to factors that have a positive influence for employee performance, so that the performance of employees of PT. Indo Dharma Transport can increase and employees will continue to improve their performance.